Study of inorganic based anti-blocks as migration control of slip additive on surface polyethylene monolayer film - Agustina, Laily Aulia; Lestari, Yeni Dwi; Adhinanda, Arrival Arsyad; Ariesta, Muhammad Naufal; Choi, Jonghyun; Prananto, Yuniar Ponco; Febriani, Rakhma (The Indonesian Chemical Society, Chapter Nusa Tenggara and The University of Mataram, 2024)
Slip migration must be controlled to maintain the performance and quality of flexible packaging. Inorganic based anti-block materials can be used to control the slip migration. This paper reported the effect of anti-block type on the inhibition of slip migration on polyethylene monolayer film. A series of formulations were made with three different anti-block additives, namely talc, natural silica, and synthetic silica, along with erucamide. The optical properties (haze) and friction properties (COF) were measured to assess the film characteristics as the development of slip migration in the presence of anti-block additives. Characterization of the anti-block material was conducted by SEM-EDX, slip additive type was examined by GC-MS, while the slip content on the surface was analysed by FTIR. The result showed that after seven days, synthetic silica anti-block gives COF up to 0.095, with the trace erucamide content on the film surface of 394 ppm, the lowest amongst other types of the anti-block used. The smaller particle size and higher silica content on synthetic silica anti-block resulted in better friction properties which act as a good barrier to limit a migration of erucamide onto the film surface.